Question
upstudy study bank question image url

Solve the equation. \[ 2 x^{3}+x^{2}=18 x+9 \]

Ask by Blake Gordon. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \(x=-3\), \(x=-\frac{1}{2}\), and \(x=3\).

Solution

Solve the equation \( 2x^{3}+x^{2}=18x+9 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2x^{3}+x^{2}=18x+9\) - step1: Move the expression to the left side: \(2x^{3}+x^{2}-\left(18x+9\right)=0\) - step2: Remove the parentheses: \(2x^{3}+x^{2}-18x-9=0\) - step3: Factor the expression: \(\left(x-3\right)\left(x+3\right)\left(2x+1\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-3=0\\&x+3=0\\&2x+1=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=3\\&x=-3\\&x=-\frac{1}{2}\end{align}\) - step6: Rewrite: \(x_{1}=-3,x_{2}=-\frac{1}{2},x_{3}=3\) The solutions to the equation \(2x^{3}+x^{2}=18x+9\) are \(x=-3\), \(x=-\frac{1}{2}\), and \(x=3\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's solve the equation \( 2 x^{3} + x^{2} = 18 x + 9 \) step by step. First, we can rearrange the equation to bring all terms to one side: \[ 2x^3 + x^2 - 18x - 9 = 0 \] Now, we can look for potential rational roots using the Rational Root Theorem, which suggests testing factors of the constant term (-9) over factors of the leading coefficient (2). The possible rational roots are \( \pm 1, \pm 3, \pm 9, \pm \frac{1}{2}, \pm \frac{3}{2}, \pm \frac{9}{2} \). After testing these values, we start with \( x = 3 \): \[ 2(3)^3 + (3)^2 - 18(3) - 9 = 2(27) + 9 - 54 - 9 = 54 + 9 - 54 - 9 = 0 \] So, \( x = 3 \) is a root. Now we can factor the polynomial using synthetic division or long division. Dividing \( 2x^3 + x^2 - 18x - 9 \) by \( x - 3 \): Using synthetic division: ``` 3 | 2 1 -18 -9 | 6 21 9 --------------------- 2 7 3 0 ``` This gives us a quotient of \( 2x^2 + 7x + 3 \). Thus, we can express the polynomial as: \[ (2x^2 + 7x + 3)(x - 3) = 0 \] Next, we'll factor \( 2x^2 + 7x + 3 \). We need to find two numbers that multiply to \( 2 \cdot 3 = 6 \) and add to \( 7 \). The numbers are \( 6 \) and \( 1 \). Thus, we can rewrite \( 7x \) as \( 6x + x \): \[ 2x^2 + 6x + x + 3 = 0 \] Now we can factor by grouping: \[ 2x(x + 3) + 1(x + 3) = 0 \] Which gives: \[ (2x + 1)(x + 3) = 0 \] So, the complete factorization is: \[ (2x + 1)(x + 3)(x - 3) = 0 \] Now we can solve for \( x \): 1. \( 2x + 1 = 0 \) leads to \( x = -\frac{1}{2} \) 2. \( x + 3 = 0 \) leads to \( x = -3 \) 3. \( x - 3 = 0 \) leads to \( x = 3 \) Thus, the solutions to the equation \( 2x^3 + x^2 = 18x + 9 \) are: \[ x = -\frac{1}{2}, \quad x = -3, \quad x = 3 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy